2010
DOI: 10.5194/bg-7-2283-2010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for greater oxygen decline rates in the coastal ocean than in the open ocean

Abstract: Abstract. In the global ocean, the number of reported hypoxic sites (oxygen <30% saturation) is on the rise both near the coast and in the open ocean. But unfortunately, most of the papers on hypoxia only present oxygen data from one or two years, so that we often lack a long-term perspective on whether oxygen levels at these locations are decreasing, steady or increasing. Consequently, we cannot rule out the possibility that many of the newly reported hypoxic areas were hypoxic in the past, and that the incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(108 citation statements)
references
References 63 publications
3
92
0
Order By: Relevance
“…Falkowski et al (2011) noted that on the 26.5 kg m 23 isopycnal in the northeast Pacific Ocean, in addition to a general decline of about 0.67mmol L 21 since 1956, the concentration of oxygen had oscillated with a period of 18.6 yr, correlated with lunar precession, through a presumed mechanism of lunar influence on tide and consequently on ventilation of the isopycnal. In their global review, Gilbert et al (2010) pointed out that more of the ocean time series showed negative trends over 1976-2000 than over 1951-1975. This could imply that hypoxia is worsening, or, alternatively, that the current downward trend is part of a longer term cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Falkowski et al (2011) noted that on the 26.5 kg m 23 isopycnal in the northeast Pacific Ocean, in addition to a general decline of about 0.67mmol L 21 since 1956, the concentration of oxygen had oscillated with a period of 18.6 yr, correlated with lunar precession, through a presumed mechanism of lunar influence on tide and consequently on ventilation of the isopycnal. In their global review, Gilbert et al (2010) pointed out that more of the ocean time series showed negative trends over 1976-2000 than over 1951-1975. This could imply that hypoxia is worsening, or, alternatively, that the current downward trend is part of a longer term cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In the open ocean, progressive deoxygenation is caused by a combination of increasing surface temperature and stratification and declining ventilation of intermediate depth water (Whitney et al 2007;Falkowski et al 2011). The decline is occurring at a greater rate in coastal waters than in the open ocean (Gilbert et al 2010) because local effects augment the global change. Inlets with restricted exchange at the entrance have always been subject to hypoxia at depth (e.g., Saanich Inlet, Herlinveaux 1962), but now the concentration of oxygen is approaching thresholds of biological tolerance in other coastal waters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bottom water oxygen concentration of shelf waters changes on such timescales (Gilbert et al, , 2010, as does iron oxide and manganese oxide concentration (Gobeil et al, 2001;Katsev et al, 2006) in sediments. In open ocean regions, changes in the ocean's dissolved oxygen are likely related to physical processes and thermohaline circulation.…”
Section: Definition Of Short-term and Long-term Environmental Factorsmentioning
confidence: 99%
“…Reduced oceanic O 2 concentrations have been reported for coastal areas in response to human-induced eutrophication (Gilbert et al, 2010), and for the open ocean as a consequence of two major processes: a warming-induced reduction in solubility and increased stratification/reduced ventilation (Helm et al, 2011). This reduction in O 2 , referred to as ocean deoxygenation, between the 1970s and the 1990s amounts to a global average reduction of −0.93 mmol m −3 (Helm et al, 2011).…”
mentioning
confidence: 99%